Answer:
y = [tex]\frac{3}{4} x[/tex]
Step-by-step explanation:
Each point is (x,y). So to find the equation, substitute both points into the given choices.
To test the first choice: y = [tex]-\frac{4}{3}x[/tex] substitute -8 into x and -6 into y
-6 = [tex]-(\frac{4}{3})(-8)[/tex]
-6(3) = (-4)(-8)
-18 ≠ 32
Since the numbers are not equal this is not the correct equation. Move on to testing the next equation in the same manner.
The third equation y = [tex]\frac{3}{4}x[/tex] satisfies both points
Test for point (-8,-6)
-6 = [tex](\frac{3}{4})(-8)[/tex]
-6(4) = (3)(-8)
-24 = -24
Test for point (12,9)
9 = [tex](\frac{3}{4})(12)[/tex]
9(4) = (3)(12)
36 = 36